Análise do custo econômico do absenteísmo de consultas no Ambulatório de Atenção Psicossocial do Hospital Universitário de Santa Maria - Oliveira, Fabrício Varoni de (2019)
Outpatient absenteeism can be considered as the absence of the user to the consultation and / or examination previously scheduled or when the health institution is communicated, however without allowing the communication of a new user to the consultation and / or examination not performed. Considering the limited capacity of care and the scarcity of resources, the health systems have aggravated their conditions due to these situations. This scenario was based on the objective of measuring the economic cost with the outpatient absenteeism of patients from the Psychosocial Care Outpatient Clinic of the University Hospital of Santa Maria (HUSM), in the period 2015-2017. This purpose was met by the use of the absorption cost method. In addition, interviews were conducted with the agents involved in the scheduling and execution of the consultations in order to obtain their perception about outpatient absenteeism and its economic repercussions. In terms of results, from the allocation of these costs, the quantitative data on the economic losses of absenteeism was obtained, which averaged R$396 thousand per year in the triennium analyzed for AAPS / HUSM. Regarding the unit cost per appointment, the results showed that the average cost per scheduled patient was R$202,92 while the average cost per patient served was R$252,95. As determinants of absenteeism, there were mainly those related to users, with emphasis on forgetfulness, lack of awareness and lack of user. Regarding the control of absenteeism and its repercussions on the institution's revenues, although the monitoring is being carried out through reports, the informational level is asymmetrical among the agents involved in the scheduling and execution process.